The Effect of Brainstorming and Recall-Based Learning on Eleventh-Grade Students’ Learning Outcomes - Sofyatun Nisa; Imam Mashuri; Rifqi Firdaus (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study aimed to compare the effectiveness of the Round Robin Brainstorming (RRB) and Memory Recall Examine (MRE) learning models in improving students’ cognitive learning outcomes in Islamic Religious Education and Character Education (PAI and BP). The research employed a quasi-experimental design using a nonequivalent group pretest–posttest approach involving 36 eleventh-grade students of SMAN Darussholah Singojuruh divided into two treatment groups. Learning outcome data were collected through cognitive tests administered before and after the intervention and analyzed using paired sample t-tests, independent sample t-tests, normalized gain (N-Gain), effect size (Cohen’s d), and coefficient of determination (R²) with SPSS 22. The findings revealed that both learning models significantly improved students’ cognitive learning outcomes (p < 0.05). The MRE group achieved higher improvement with an N-Gain score of 0.62 and a very large effect size (Cohen’s d = 1.74), while the RRB group showed moderate improvement with an N-Gain score of 0.45 and Cohen’s d = 0.65. The R² value of 0.65 indicated that 65% of the variance in learning outcomes was explained by the implemented learning models. These findings suggest that MRE is more effective in improving cognitive learning outcomes, whereas RRB better promotes student engagement and collaborative participation during structured group discussions.